2012
DOI: 10.1200/jco.2011.40.0846
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Unit Outcomes Among Patients With Lung Cancer in the Surveillance, Epidemiology, and End Results–Medicare Registry

Abstract: A B S T R A C T PurposeLung cancer is the leading cause of cancer-related mortality. Intensive care unit (ICU) use among patients with cancer is increasing, but data regarding ICU outcomes for patients with lung cancer are limited. Patients and MethodsWe used the Surveillance, Epidemiology, and End Results (SEER) -Medicare registry (1992 to 2007) to conduct a retrospective cohort study of patients with lung cancer who were admitted to an ICU for reasons other than surgical resection of their tumor. We used log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
67
3
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 36 publications
6
67
3
5
Order By: Relevance
“…It also constitutes a significant proportion in the ICU mortality. Previous studies showed poor outcomes in lung cancer patients admitted to the ICU and most notably those requiring mechanical ventilation (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 98%
“…It also constitutes a significant proportion in the ICU mortality. Previous studies showed poor outcomes in lung cancer patients admitted to the ICU and most notably those requiring mechanical ventilation (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 98%
“…2 Briefl y, patients were eligible if they had received a diagnosis of lung cancer between 1992 and 2005 (n 5 324,509) and they were also enrolled in Medicare during that time. We excluded (1) patients whose lung cancer was diagnosed at autopsy or on a death certifi cate only (n 5 7,650), (2) those with an in situ stage (n 5 195), (3) patients younger than 66 years old at the time of diagnosis (n 5 56,048), (4) those who were eligible for Medicare benefi ts because of disability (n 5 25,078), and (5) those enrolled in Medicare-managed care plans between 1 year prior to and 5 years aft er a lung cancer diagnosis (n 5 59,629) because these patients may have incomplete claims, and are, typically, excluded in studies using Medicare claims.…”
Section: Patient Samplementioning
confidence: 99%
“…1,2 Despite signifi cant advancements in the treatment of lung cancer and in the care of critically ill patients over the last 15 years, these survival statistics remain unchanged. 2 When confronting the end of life, the vast majority of patients with lung cancer would rather forego aggressive nonpalliative care, stating that they would prefer to die at home.…”
mentioning
confidence: 99%
See 2 more Smart Citations